Application of Proknow-C for systematic literature review on: time delay in the reverse logistics network project of residual cooking oil - Zioto, Alyson Martins; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2023)
Residual cooking oil if disposed of incorrectly, coming into contact with water or soil, because it is a substance that has no solubility can cause pollution both in nature and in cities. In view of the above, the objective of this study is to apply the methodology called ProKnow-C based on the research theme: Time delay in the design of a reverse logistics network for cooking oil. The ProKnow-C methodology is a systematic literature review tool, to obtain a theoretical foundation for the study in question, thus it is possible to perform a more careful analysis of the quality of the content, establishing parameters for inclusion or exclusion of articles and filtering the most relevant articles. Initially, 680 articles were collected for the database, using the keywords corresponding to the research theme, then filters were performed establishing the necessary criteria, such as: redundancy, alignment of the title, scientific recognition, prominent authors and more recent publications, then it was possible to carry out the exclusion of less relevant articles. After the exclusion of the articles based on the previous criteria, eight articles remained, and it was analyzed that the articles have sufficient grounds for construction and are relevant to the main theme. Thus, it was observed that the methodology applied was crucial to the structuring and theoretical foundation for the construction of the work.